"A Whole Other Layer of Complexity": Black Transgender Men's Experiences. Issue Volume 14:Issues 3(2020) (3rd August 2020) - White, Mickey E.; Cartwright, Angie D.; Reyes, Ana G.; Morris, Hailey; Lindo, Natalya A.; Singh, Anneliese A.; McKinzie Bennett, Caitlyn
Abstract: Black transgender men are exposed to systems of oppression such as racism and cissexism at unique intersections of marginalized racial and gender identities, yet their experiences within such systems are not well understood. In this qualitative study, 10 Black transgender men were interviewed and six major themes were identified: developing an empowered view of self, navigating double consciousness, having a target on your back, strategies of resilience, culture of silence, and finding quality care.